"Sport is community:" An exploration of urban Aboriginal peoples' meanings of community within the context of sport. (May 2015) - McHugh, Tara-Leigh F.; Coppola, Angela M.; Holt, Nick L.; Andersen, Chris
Abstract: Objectives: The purpose of this study was to better understand the meanings of community, particularly as it is understood within the context of sport, for urban Aboriginal youth and adults in Edmonton, Alberta. Design: A community-based participatory research (CBPR) approach was used to guide this research. Method: One-on-one interviews were conducted with 18 Aboriginal youth and adults. Data was analyzed usingElo and Kyngäs' (2008) process of content analysis. The integrated indigenous-ecological model was used as a framework for data analysis and the interpretation of findings. Results: Findings are represented by five themes that are supported by direct quotes from participants. Participants described community as: (1) belonging, (2) family and friends, (3) supportive interactions, (4) sport, and (5) where you live and come from. Conclusions: Findings from this research suggest that urban Aboriginal youth identify with a number of different communities, and their complex meanings of communities are comprised of various interpersonal level factors. The knowledge shared by participants provides necessary insights into meanings of community, which are necessary for ensuring that community-driven and community-based sport programs are relevant to Aboriginal youth. Highlights: Findings were interpreted within the integrated indigenous-ecological model. Urban Aboriginal peoples may feel connected to a broader Aboriginal community. Indigenous perspectives should be central in sport research with Aboriginal peoples. Sport in itself may be understood as community.